Kajian Mineral Fraksi Pasir pada Andisol yang Berkembang dari Hasil Erupsi Gunung Tangkuban Parahu dan Gunung Patuha, Jawa Barat - Rina Devnita; Mahfud Arifin; Ridha Hudaya (Soilrens, 2016)
Mineral content of the soil determines various properties including nutrient that can bereleased during the weathering process. The research to identify the minerals in Andisol developedfrom the eruption of Mt. Tangkuban Parahu and Mt. Patuha had been conducted to determine theminerals content in the sand fraction. This research was conducted in several steps: the field survey,soil sampling, and laboratory analysis. The field locations were in the forest of Cikole, Lembang,West Java derived from the eruption Mt. Tangkuban Parahu and in the forest of Patengan,Rancabali, West Java derived from the eruption of Mt. Patuha. Sand fraction was separated from siltand clay by wet sieving method, using the 50 micron siever. Microscopic observation for identifyingthe minerals was done with polarization microscope to the color, luster, shape of grains and crystals,cleavage, hardness, transparency, translucent, and magnetic properties. The results showed that thesand fraction of Andisol derived from Mt. Tangkuban Parahu and Mt. Patuha had the mineralcontent as hypersthene, diopside, orthoclase, oligoclase, anorthite, andesine, hornblende, biotite,quartz, corundum, magnetite dan sulphur, showed that the weathering those minerals cancontribute some nutrients like Mg, Ca, K Fe, and S to the soilKey words: hyperstene, diopside, anorthite, hornblende, biotite